Gender norms and family planning amongst pastoralists in Kenya: a qualitative study in Wajir and Mandera. Issue 1 (31st December 2022) - Kenny, Leah; Lokot, Michelle; Bhatia, Amiya; Hassan, Rahma; Pyror, Shannon; Dagadu, Nana Apenem; Aden, Abdullahi; Shariff, Abdalla; Bacchus, Loraine J.; Hossain, Mazeda; Cislaghi, Beniamino
Abstract: There is growing recognition among global health practitioners of the importance of rights-based family planning (FP) programming that addresses inequities. Despite Kenya achieving its national FP target, inequities in access and use of modern FP remain, especially amongst marginalised nomadic and semi-nomadic pastoralist communities. Few studies explore norms affecting FP practices amongst nomadic and semi-nomadic pastoralists and how these can influence social and behaviour change (SBC) interventions. We carried out 48 in-depth interviews and 16 focus group discussions with women and men from pastoralist communities in North Eastern Kenya in November 2018. Data were analysed thematically. Results from focus groups and interviews confirmed themes, while allowing differences between the qualitative approaches to emerge. We found that large family size was a descriptive and injunctive norm in both nomadic and semi-nomadic communities. The desire for around 10 children was sustained by religious beliefs and pastoralist ways of living. Despite a desire for large families, maintaining child spacing was encouraged and practised through breastfeeding and sexual abstinence. Most participants viewed modern FP negatively and as something used by "others". However, it was acceptable in order to prevent severe negative health outcomes. Future FP research to inform interventions should continue to consider community fertility preferences and the rationale for these, including norms, religion and power dynamics. Targeted qualitative social norms research could inform multi-component SBC interventions in this context.